Virus detectives test whole-body scans in search of HIV's hiding places. (25th October 2018) - Reardon, Sara
To prevent the virus from rebounding after drug therapy, researchers must first map where it lurks in the body. To prevent the virus from rebounding after drug therapy, researchers must first map where it lurks in the body.